2020
DOI: 10.1080/13811118.2020.1746942
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injurious Thoughts and Behaviors Among College Students: A Latent Class Analysis

Abstract: This study explored emerging typologies of self-injurious thoughts and behaviors and how they relate to known psychological and cognitive correlates. Latent class analysis was employed to identify subgroups of college students (n=626, mean age=20, 73% female, and 83% White) based on history of self-injurious thoughts and behaviors. Differences among classes were tested to examine their associations with suicidal ideation, fearlessness of death, depression/hopelessness, thwarted belongingness, problems with alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
2
5
0
1
Order By: Relevance
“…Items from the measure include statements such as "Sometimes I have thoughts of killing myself" and "I am having thoughts of suicide, but these thoughts are somewhat under my control". In a previous study that examined suicide risk among college students, the scale demonstrated good internal reliability (α = 0.89) [50]. The HDSQ-SS scale demonstrated excellent internal consistency (α = 0.98) in the current study.…”
Section: Methodssupporting
confidence: 59%
“…Items from the measure include statements such as "Sometimes I have thoughts of killing myself" and "I am having thoughts of suicide, but these thoughts are somewhat under my control". In a previous study that examined suicide risk among college students, the scale demonstrated good internal reliability (α = 0.89) [50]. The HDSQ-SS scale demonstrated excellent internal consistency (α = 0.98) in the current study.…”
Section: Methodssupporting
confidence: 59%
“…Researchers identified three classes in a sample of first-year undergraduates: an infrequent NSSI/not high risk for suicidal behavior group, a frequent NSSI/not high risk for suicidal behavior group, and a frequent NSSI/high risk for suicidal behavior group (Hamza & Willoughby, 2013 ). Results from an LCA in a college sample supported a 3-class solution as well, with students classified as being likely to have no history of any self-injurious thoughts and behaviors, a history of all self-injurious thoughts and behaviors measured, or a history of suicidal ideation, plan, and nonsuicidal self-injurious thoughts and behaviors, but not suicide attempt (Marraccini et al ( 2021 )). Notably, in all previous studies, individuals in the classes with the most frequent nonsuicidal self-injury and the highest levels of suicidality had the worst clinical outcomes.…”
Section: Introductionmentioning
confidence: 88%
“…Person‐centered methods like latent class analysis (LCA) enable the systematic identification of distinct profiles for patients with suicidal behaviors. Yet, the few studies that assessed profiles for suicidal behaviors were conducted only among adolescents (Jiang et al, 2010; King et al, 2020; Tairi et al, 2018), young adults (Hamza & Willoughby, 2013; Marraccini, 2021) or military personnel (Allan et al, 2020; Skopp et al, 2016). Even fewer studies investigated profiles of patients who used ED (King et al, 2020) or were hospitalized (King et al, 2020; Rapeli & Botega, 2005; Tairi et al, 2018) for suicidal behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Even fewer studies investigated profiles of patients who used ED (King et al, 2020) or were hospitalized (King et al, 2020; Rapeli & Botega, 2005; Tairi et al, 2018) for suicidal behaviors. These studies produced profiles revealing higher rates of suicidal behaviors among women (Jiang et al, 2010; Marraccini, 2021; Xiao & Lindsey, 2021), sexual minority individuals (e.g., gays, lesbians) (Jiang et al, 2010; Xiao & Lindsey, 2021), and victims of prior physical or sexual abuse (Jiang et al, 2010; King et al, 2020). MD most often associated with a higher incidence of suicidal behaviors were depressive (Jiang et al, 2010; Marraccini, 2021; Rapeli & Botega, 2005), adjustment (Rapeli & Botega, 2005), mood (King et al, 2020; Tairi et al, 2018), and personality disorders (Tairi et al, 2018), and SRD (Allan et al, 2020; King et al, 2020; Marraccini, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation